The impact of weevil predation on seed viability and agronomic performance of cowpeas, Vigna unguiculata L. (Walp) - Dlamini, Welile Mlando (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.